1980
DOI: 10.1111/j.1365-2265.1980.tb02705.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Prolactin Secretion by Nomifensine in Man

Abstract: Serum prolactin, TSH and GH levels were measured in thirty healthy volunteers in fasting conditions and following oral administration of 200 mg nomifensine. In addition, the effect of the drug on serum prolactin and TSH response to synthetic TRH was studied in twenty normal subjects. Inhibition of endogenous catecholamine reuptake by nomifensine significantly inhibited prolactin release whereas it had no effect on TSH and GH levels. Nomifensine administration had no appreciable effect on the TRH-induced releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

1980
1980
1995
1995

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
2
2
1
Order By: Relevance
“…Our data seem to be in contrast with those reported in the literature concerning the behavior of TSH after NOM [16,19]. Furthermore, the experiments carried out untill now were performed with methods different from ours: a different choice of TRH administration time [19], lack of a concomitant placebo test [16].…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Our data seem to be in contrast with those reported in the literature concerning the behavior of TSH after NOM [16,19]. Furthermore, the experiments carried out untill now were performed with methods different from ours: a different choice of TRH administration time [19], lack of a concomitant placebo test [16].…”
Section: Discussioncontrasting
confidence: 55%
“…Furthermore, the experiments carried out untill now were performed with methods different from ours: a different choice of TRH administration time [19], lack of a concomitant placebo test [16]. In addition, both the differ ent make-up of the cases studied on the one hand and the fact that TSH basal titers are per se usually very low even in normal subjects on the other, may have contributed to masking the inhibitory phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in agreement with previous data of ours and of others [Masala et al 1980;Scanlon et al 19771, no effect on TRH-induced prolactin secretion was observed. Experimental studies have shown that nomifensine is able to interfere with the central reuptake of dopamine, norepinephrine, and serotonin to different extents [Gerhards, 1977;Schacht et al, 1977;Schacht and Heptner, 19741.…”
Section: Discussionsupporting
confidence: 94%
“…The present study shows, on the one hand, that inhibition of endogenous catecholamine reuptake by nomifensine, given at doses similar to clinical treatment for depression [Amin et al 1978: Clerc and Cayreyre, 19781, is able to suppress completely the prolactinreleasing effect exerted by hypoglycaemia in man. On the other hand, in agreement with previous data of ours and of others [Masala et al 1980;Scanlon et al 19771, no effect on TRH-induced prolactin secretion was observed. Experimental studies have shown that nomifensine is able to interfere with the central reuptake of dopamine, norepinephrine, and serotonin to different extents [Gerhards, 1977;Schacht et al, 1977;Schacht and Heptner, 19741.…”
Section: Discussionsupporting
confidence: 94%
“…JOHNSTONE & I.N. FERRIER prolactin following the administration of a single 200 mg dose (Muller, Genazzi & Murru, 1978; Masala, Magna, Devella, Delitala & Novasio, 1980) although results of another study do not support this (Dunne, Walker, Cowden & Ratcliffe, 1979). Antidepressants show few consistent effects upon growth hormone secretion.…”
Section: Antidepressantsmentioning
confidence: 99%